2019
DOI: 10.3390/ma12244161
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Economic Analysis of FDM, SLS and MJF Additive Manufacturing Technologies

Abstract: In this study, the authors present a comparative analysis of different additive manufacturing (AM) technologies for high-performance components. Four 3D printers, currently available on the Italian national manufacturing market and belonging to three different AM technologies, were considered. The analysis focused on technical aspects to highlight the characteristics and performance limits of each technology, economic aspects to allow for an assessment of the costs associated with the different processes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 33 publications
(21 reference statements)
0
36
0
Order By: Relevance
“…Polymers have also been used as a manufacturing material for 3D structures for bone regeneration. They were used individually, mainly in the early years of development of additive manufacturing technologies (1984) [ 15 , 17 , 52 ], and more recently associated with nanoparticles [ 45 ], antibiotics [ 39 ], and other substances such as peptides and dopamine [ 16 ]. Their efficacy and biocompatibility have been proven in in vivo studies with experimental animals such as Beagle dogs [ 17 ] and New Zealand rabbits [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Polymers have also been used as a manufacturing material for 3D structures for bone regeneration. They were used individually, mainly in the early years of development of additive manufacturing technologies (1984) [ 15 , 17 , 52 ], and more recently associated with nanoparticles [ 45 ], antibiotics [ 39 ], and other substances such as peptides and dopamine [ 16 ]. Their efficacy and biocompatibility have been proven in in vivo studies with experimental animals such as Beagle dogs [ 17 ] and New Zealand rabbits [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have compared the outcomes gathered by several techniques. Silva [ 50 ] showed that the precision of 3D printing and SLS was comparable and acceptable in both cases; Salmi [ 51 ] highlighted the PolyJet over the previous two in terms of precision, and Tagliaferri [ 52 ] indicated that, among the FFF, SLS and MJF, the FFF was the less convenient option due to the high printing time and environmental impact, which was minimal with MJF ( Table 2 ). Within the additive manufacturing methods, in this review of the literature we found that some of them, such as stereolithography [ 33 , 34 ] and selective laser sintering [ 35 ], have been shown to be successful with regard to bone regeneration through studies in humans, which are the most relevant in terms of practical clinical effects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations